1984
DOI: 10.1515/zna-1984-1217
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption Behavior of Water and Some Organic Liquids in the Near Infrared Studied by Photoacoustic Spectroscopy

Abstract: T h e A b s o rp tio n B e h a v io r o f W a te r a n d S o m e O r g a n i c L iq u id s in th e N e a r I n fr a re d S tu d ie d by P h o

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…800nm with an EG & G, Princeton Applied Research Model 6001 photoacoustic spectrometer, as described elsewhere. 29 The samples were investigated at normal pressure and room temperature (293 K).…”
Section: Methodsmentioning
confidence: 99%
“…800nm with an EG & G, Princeton Applied Research Model 6001 photoacoustic spectrometer, as described elsewhere. 29 The samples were investigated at normal pressure and room temperature (293 K).…”
Section: Methodsmentioning
confidence: 99%
“…The basic technique [1,2] utilized sealed cells and conventional light sources with mechanical chopping to modulate incident light which, via optical absorption and resultant heating, caused detectable bulk expansion of the sample. The technique subsequently found wider application with the availability of xenon arc lamps for the study of organometallic compounds [3], organic liquids [4] and rare earth oxides [5]. Argon lasers have been used to study analytes in liquids; sensitivities of parts per trillion have been reported [6] but the spectroscopy was restricted by the limited wavelength tuneability.…”
Section: Photoacoustic Spectroscopymentioning
confidence: 99%